New applications of intracardiac echocardiography: assessment of coronary blood flow by colour and pulsed Doppler imaging in dogs. (1st September 2002) - Teragaki, M; Toda, I; Takagi, M; Fukuda, S; Ujino, K; Takeuchi, K; Yoshikawa, J
Abstract : Objective: To explore the application of a new 10 French intracardiac echocardiography (ICE) catheter with phased array and Doppler capable transducer for the assessment of epicardial and intramyocardial coronary blood flow. Methods: The coronary arteries were detected by cross sectional imaging in seven closed chest dogs, and coronary blood flow visualised by colour Doppler. Blood flow velocities were recorded by pulsed Doppler at baseline for reproducibility of repeated measurements, and during hyperaemia for coronary flow reserve measurements. Comparisons were made with Doppler guide wire data obtained simultaneously. Intramyocardial coronary artery blood flow was assessed by colour flow mapping, and the blood flow velocities recorded using pulsed Doppler at baseline and during hyperaemia. Results: Seven left main, six left anterior descending, seven left circumflex, and five right coronary arteries were visualised in the seven animals by cross sectional or colour Doppler imaging. Repeated measurements of coronary flow velocity showed a good correlation (mean diastolic velocity, r = 0.93, n = 22, p < 0.0001; peak diastolic velocity, r = 0.96, n = 22, p < 0.0001, respectively). Intraobserver/interobserver variability was satisfactorily low. Coronary flow reserve from ICE correlated highly with the value obtained from the Doppler guide wire ( r = 0.90, n = 26, p < 0.0001). Intramyocardial coronary blood flow was identified in all seven dogs, and flow velocities were recorded at baseline and during hyperaemia in four animals. Conclusions: This new ICE catheter provides high quality diagnostic resolution. It is useful for coronary blood flow assessment.